A combination of spectral graph theory and quantum genetic algorithm to find relevant set of electrodes for motor imagery classification - Kirar, Jyoti Singh; Agrawal, R.K. (Applied soft computing, 2020)
At present, more number of electrodes are used to develop brain computer interface (BCI) devices based on motor imagery. However, the number of trials for a given subject is usually less. Under this situation, the performance of motor imagery task classification may degrade. In this research work, we propose a combination of graph theoretic spectral method and quantum genetic algorithm (QGA) to obtain a subset of relevant and non-redundant electrodes for effective motor imagery task classification. Stationary Common Spatial Pattern method, which can handle non-stationarity issue, is used for extraction of features from the reduced set of electrodes. Support Vector Machine (SVM) is used as a classifier. Improvement in classification performance on publicly available dataset signifies efficacy of the proposed method. Friedman statistical test demonstrates that the performance of the proposed method is significantly better in comparison to existing CSP and its variants. [Display omitted] •Provide a more robust method that identify a subject specific reduced subset of relevant electrodes.•Uses a combination of graph theory and Quantum Genetic Algorithm for electrode subset selection.•Proposed method performs outstandingly on publicly available datasets.•Proposed method is statistically significant and superior in comparison to existing methods.